Undescribed polyether ionophores from Streptomyces cacaoi and their antibacterial and antiproliferative activities. (March 2022) - Gezer, Emre; Üner, Göklem; Küçüksolak, Melis; Kurt, Mustafa Ünver; Doğan, Gamze; Kırmızıbayrak, Petek Ballar; Bedir, Erdal
Abstract: Polyether ionophores represent a large group of naturally occurring compounds mainly produced by Streptomyces species. With previously proven varieties of bioactivity including antibacterial, antifungal, antiparasitic, antiviral and anti-tumor effects, the discovery of undescribed polyethers leading to development of efficient therapeutics has become important. As part of our research on polyether-rich Streptomyces cacaoi, we previously performed modification studies on fermentation conditions to induce synthesis of specialized metabolites. Here, we report four undescribed and nine known polyether compounds from S . cacaoi grown in optimized conditions. Antimicrobial activity assays revealed that four compounds, including the undescribed (6 ), showed strong inhibitory effects over both Bacillus subtilis and methicillin-resistant Staphylococcus aureus (MRSA) growth. Additionally, K41-A and its C15-demethoxy derivative exhibited significant cytotoxicity. These results signified that selectivity of C15-demethoxy K41-A towards cancer cells was higher than K41-A, which prompted us to conduct mechanistic experiments. These studies showed that this uninvestigated compound acts as a multitarget compound by inhibiting autophagic flux, inducing reactive oxygen species formation, abolishing proteasome activity, and stimulating ER stress. Consequently, the optimized fermentation conditions of S . cacaoi led to the isolation of undescribed and known polyethers displaying promising activities. Graphical abstract: Thirteen polyether compounds were isolated from S. cacaoi grown in optimized conditions and their antibacterial, and cytotoxic activities were evaluated. Image 1 Highlights: Four undescribed and nine known polyether compounds were isolated from S. cacaoi. Growth inhibitory effects over bacteria and cancer cells were observed. Amicetose moiety and O -methylation on the ring A are important for bioactivities. Compound 4 showed selective cytotoxicity against cancer cells. Compound 4 inhibited autophagy as well as induced UPR and ROS production.